2016
DOI: 10.1021/acs.inorgchem.6b00701
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting Photo- and Electroluminescence Properties of FIrpic Organic Crystals

Abstract: In this work, we investigate the optical and structural properties of the well-known triplet emitter bis(4',6'-difluorophenylpyridinato)-iridium(III) picolinate (FIrpic), showing that its ability to pack in two different ordered crystal structures promotes attractive photophysical properties that are useful for solid-state lighting applications. This approach allows the detrimental effects of the nonradiative pathways on the luminescence performance in highly concentrated organic active materials to be weakene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 27 publications
(49 reference statements)
3
7
0
Order By: Relevance
“…As far as the nanostructures are concerned, in the case of FI-Nps and PPY-Nps the aggregation induces both a change in the relative intensity of the vibronic peaks and the appearance of a broad shoulder extending to lower energy (Figure A,B). The presence of a lower-energy band has been recently reported for highly doped FI films, and it was ascribed to the interaction between nearby cyclometalating ligands in the FI crystalline domains of the films . A similar scenario can be proposed for these highly crystalline nanoparticles, further corroborating the hypothesis that the observed changes in the emission properties are due to stronger intermolecular interactions present in the tightly packed core of the nanoparticles.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…As far as the nanostructures are concerned, in the case of FI-Nps and PPY-Nps the aggregation induces both a change in the relative intensity of the vibronic peaks and the appearance of a broad shoulder extending to lower energy (Figure A,B). The presence of a lower-energy band has been recently reported for highly doped FI films, and it was ascribed to the interaction between nearby cyclometalating ligands in the FI crystalline domains of the films . A similar scenario can be proposed for these highly crystalline nanoparticles, further corroborating the hypothesis that the observed changes in the emission properties are due to stronger intermolecular interactions present in the tightly packed core of the nanoparticles.…”
Section: Resultssupporting
confidence: 83%
“…In particular, FI-Nps and PPY-Nps appear to have a higher propensity to form highly ordered nanocrystals than MDQ-Nps which displays only one narrow reflection peak at 11.5° (2-theta) in the diffraction pattern. The comparison with diffraction data previously reported for FIrpic polymorphs confirms that FIrpic nanoparticles reproducibly crystallize in the monoclinic form of methanol solvate crystals, well-known to be stable also in the absence of solvent molecules . This evidence provided us further information about the structural organization of the molecules within the nanoparticle, suggesting that π–π stacking interactions among the phenylpyridine moieties play an important role in driving the assembly and stabilizing the nanostructure.…”
Section: Resultssupporting
confidence: 79%
“…Cationic cyclometalated Ir complexes with pendant ligands that show dual emission from ligand-centred (LC) and interligand charge transfer (ILCT) states have been synthesised and shown to function as sensors for biomolecules. 11 An iridium complex containing a dibenzoylmethane ancillary ligand has been reported to exhibit different emission spectra from two distinct polymorphs, related to the difference in π-stacking interactions in the solid state. 12 Iridium complexes have also been incorporated into polymer chains containing other emissive materials of different colours.…”
Section: Introductionmentioning
confidence: 99%
“…The target heteroleptic picolinate iridium complexes 2-6 were then synthesised (Scheme 1, Scheme 2) via the standard method. 26,27 Reaction of the ligands (7)(8)(9)(10)(11) with IrCl3•3H2O gave yellow precipitates presumed to be the intermediate μdichloro-bridged dimers. Picolinic acid was added and the solution heated to 110-130 ⁰C.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Device-ND achieved the low light threshold voltage V T of 2.4 V, high luminance maximum (L max ) of 4456 cd/m 2 , and high current efficiency of 2.9 cd/A by adopting the NiO x NPs and the additive-assisted EML that gave a better hole transporting and high radiative recombination rate, respectively. It can be clearly observed that the threshold of the minority carrier (holes) injection Coatings 2020, 10, 336 6 of 8 at 2.4 V and the onset of majority carrier (electrons) injection at~2.3 V matched pretty well, which suggests that those negative effects such as Auger recombination (trions) and improper shift of exciton recombination zone can therefore be prevented [29,30]. Overall, compared with Device-PA, Device-ND had roughly 17-and 94-fold increased L max and η CE , respectively.…”
Section: Resultsmentioning
confidence: 87%